Down to the sea in ships - Beheim, Eric
The ten-minute sequence from Down to the Sea in Ships (1922) documents an authentic whale hunt from the 1878 wooden ship Wanderer out of New Bedford, Massachusetts. The cameramen risk their lives to capture practices unchanged since Herman Melville immortalized them in Moby Dick. Music by Dennis James. [Cover]
Sequenz von 10 Minuten aus dem 82 minütigen Spielfilm "Down to the sea in ships"
10 Min., s/w., stumm
Orig.: USA 1922